Advanced coatings for buildings (2020)
Based on five Special Issues in Coatings, this e-book contains a series of fifteen articles demonstrating actual perspectives and new trends in advanced coatings in buildings. Innovative materials and multiperformance solutions provide a basis, contributing also to better protection of buildings’ surfaces during the service life, and users’ wellbeing.